Insertions into azatitanacyclobutenes: New insights into three-component coupling reactions involving imidotitanium intermediates - Vujkovic, N; Fillol, J; Ward, B; Wadepohl, H; Mountford, P; Gade, L (2008)
Reaction of the titanium imido complexes [Ti(NR)(N2XylNpy)(L)] (N2XylNpy = MeC(2-C5H4N) {CH2N(3,5-C6H 3Me2)}2) with aryl acetylenes afforded the {2+2} cycloaddition products [Ti(N2XylN py){κ2-N(tBu)CH=CAr}] (Ar = Ph: 1a, Tol: 1b (Tol = 4-C6H4Me)). Complex 1a was found to insert sulfur and selenium atoms into the Ti-C bond of the strained azatitanacyclobutene unit to give the five-membered metallacyclic systems [Ti(N2XylNpy){κ2-N(tBu)CH= C(Ph)E}] (E = S: 2, Se: 3). Likewise, isonitriles were found to insert into the Ti-C bonds to give [Ti(N2XylNpy) {κ2-N(tBu)CH=C(Ar)C=NR}] (Ar = Ph, R = xylyl: 4, Cy: 5, tBu: 6a; Ar = C6H5Me, R = tBu: 6b), one example of which (4) has been characterized by X-ray crystallography. The latter species is thought to be a key intermediate in the titanium-mediated three-component coupling of primary amines with acetylenes and isonitriles ("iminoamination"). Reaction of [Ti(N2XylN py){κ2-N(tBu)CH=C(Ph)C=NR}] with tBuNH2 gave tBuN=CHC(Ph)CHNHR, which have been previously identified as the major reaction products in the catalytic aminoamination of alkynes. © 2008 American Chemical Society.